Little killers : the ferocious lives of puny predators - Collard, Sneed B. (Millbrook Press, 2022)
"Meet some of the world's most impressive predators! Small creatures can make a huge impact, changing ecosystems, controlling pests, and even taking down much larger creatures. Discover the amazing lives of these voracious killers"--